The Role Of Student In Preventing Sexual Violence Based On PERMENDIKBUDRISTEK No. 30 Of 2021 And Review Of Political Jurisprudence In Fiqh - Muhtaj, Majda El; Hermansyah, Hermansyah (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2022)
This study aims to find out how the role of students is very important in preventing violence and sexual harassment in Islamic-based universities. then in conditions like this it is necessary to issue a regulation made by the government such as Permendikbudristek No. 30 of 2021, and one of the obligations of students is to give their best efforts during class time to seek to improve existing problems on campus and provide concrete evidence to the community for the important role of students. In fact, sexual violence is rife in the educational environment which is dominated by educated and intellectual people. In this case, not only the role of students is needed but the role of lecturer collaboration is also very important in providing direction and guidance regarding the prevention and handling of sexual violence by students in the campus area. It is also important to know how fiqh siyasa relates to fiqh siyasa dusturiyah which discusses statutory rules, in the case of fiqh siyasa rules are made in the interest of the common good. In this study the authors took an empirical juridical research methodology with a qualitative approach, empirical juridical research which in other words is a type of sociological legal research and can be referred to as research in the field, which examines the legal provisions that apply and what has happened in people's lives.